2005
DOI: 10.1128/aem.71.11.6736-6745.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Biochemical Properties, and Distribution of Mycobacterial Haloalkane Dehalogenases

Abstract: Haloalkane dehalogenases are enzymes that catalyze the cleavage of the carbon-halogen bond by a hydrolytic mechanism. Genomes of Mycobacterium tuberculosis and M. bovis contain at least two open reading frames coding for the polypeptides showing a high sequence similarity with biochemically characterized haloalkane dehalogenases. We describe here the cloning of the haloalkane dehalogenase genes dmbA and dmbB from M. bovis 5033/66 and demonstrate the dehalogenase activity of their translation products. Both of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…Although there is only limited information on the diversity of bacterial haloacetic acid dehalogenases, the homologous proteins (or the corresponding genes) of haloalkane dehalogenases LinB from Sphingobium japonicum strain UT26 (Nagata et al, 1993) have been found in various bacteria, including Mesorhizobium loti strain MAFF303099 (DmlA), Bradyrhizobium japonicum USDA110 (DbjA) (Sato et al, 2005), and Mycobacterium avium strain N85 (DhmA) (Jesenska et al, 2005). The enzyme activities of the haloalkane dehalogenases toward various substrates have been assessed, and it was reported that DbjA showed higher dehalogenation activity for substrates carrying a bulky substituent at the β position than did LinB (Sato et al, 2005).…”
Section: Cloning and Dna Sequencing Of Group II Dehalogenase-encodingmentioning
confidence: 99%
“…Although there is only limited information on the diversity of bacterial haloacetic acid dehalogenases, the homologous proteins (or the corresponding genes) of haloalkane dehalogenases LinB from Sphingobium japonicum strain UT26 (Nagata et al, 1993) have been found in various bacteria, including Mesorhizobium loti strain MAFF303099 (DmlA), Bradyrhizobium japonicum USDA110 (DbjA) (Sato et al, 2005), and Mycobacterium avium strain N85 (DhmA) (Jesenska et al, 2005). The enzyme activities of the haloalkane dehalogenases toward various substrates have been assessed, and it was reported that DbjA showed higher dehalogenation activity for substrates carrying a bulky substituent at the β position than did LinB (Sato et al, 2005).…”
Section: Cloning and Dna Sequencing Of Group II Dehalogenase-encodingmentioning
confidence: 99%
“…The dehalogenation of chlorinated alcohol ethers by these enzymes, however, may be a novel reaction. The involvement of multiple dehalogenases in the same strain also cannot be ruled out completely (7,9).…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, however, enzymatic reactions may facilitate transformation of the hemiacetal (17). An O-dealkylation mechanism has been suggested for BCEE degradation by a Rhodococcus strain (9) and Rhodococcus strain DTB (12). In the case of chlorinated ethers like BCEE, however, additional biological reactions may be required prior to ether scission.…”
mentioning
confidence: 99%
“…obvious (15,39,40), (iii) genetic engineering of mycobacteria is complicated due to the extremely slow growth and high pathogenicity of the organisms, and (iv) it was the enzyme least affected by the ligand-based inhibitors.…”
Section: Figmentioning
confidence: 99%
“…For instance, it is undoubtedly interesting that the plant pathogen Agrobacterium tumefaciens C58 carries the HLDencoding gene datA on its tumor-inducing plasmid while there is no clear link between HLD activity and tumorigenesis (14). Similarly, the presence of three different HLD genes in the genome of the human pathogen Mycobacterium tuberculosis H37Rv (15) suggests that HLDs are important for its survival, but it is not immediately obvious why an organism that colonizes human tissues would require enzymes that cleave carbon-halogen bonds. One way to study the natural function of an enzyme is to use specific inhibitors.…”
mentioning
confidence: 99%